2010
DOI: 10.2527/jas.2009-2359
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming: The concept, large animal models, and the key role of uteroplacental vascular development1,2

Abstract: Developmental programming refers to the programming of various bodily systems and processes by a stressor of the maternal system during pregnancy or during the neonatal period. Such stressors include nutritional stress, multiple pregnancy (i.e., increased numbers of fetuses in the gravid uterus), environmental stress (e.g., high environmental temperature, high altitude, prenatal steroid exposure), gynecological immaturity, and maternal or fetal genotype. Programming refers to impaired function of numerous bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
116
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 63 publications
1
116
0
4
Order By: Relevance
“…Research has suggested that an insult to nutrition of the dam during gestation can influence the long-term health and productivity of offspring through a process that has been termed fetal, or developmental, programming (Barker, 2004;Wu et al, 2006;Reynolds et al, 2010). A growing body of evidence suggests that gestational nutrition can alter offspring body composition and growth, hormonal balance, cardiovascular development, metabolic function, neonatal health, organ development and function (Wu et al, 2006;Long et al, 2009), and gene expression (Long et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that an insult to nutrition of the dam during gestation can influence the long-term health and productivity of offspring through a process that has been termed fetal, or developmental, programming (Barker, 2004;Wu et al, 2006;Reynolds et al, 2010). A growing body of evidence suggests that gestational nutrition can alter offspring body composition and growth, hormonal balance, cardiovascular development, metabolic function, neonatal health, organ development and function (Wu et al, 2006;Long et al, 2009), and gene expression (Long et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal environment during gestation affects the developing fetus, which may result in impaired development and potential long-term consequences (Godfrey and Barker, 2000;Wu et al, 2006;Reynolds et al, 2010) that can occur even when birth weight is unaffected (Ford et al, 2007;Martin et al, 2007;Larson et al, 2009). This concept of developmental programming often focuses on gestation, although a growing body of literature suggests that postnatal environment may also program later growth and development (Greenwood and Cafe, 2007;Patel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cattle breeding has an increasing demand for animals of high genetic value, thus boosting the use of animal breeding biotechnologies. Changes arising from the fetal period may harm the reproductive system in adulthood by preventing phenotypic expression in the animal with a given genotypic potential, thus compromising genetic selection for insemination programs (REYNOLDS et al, 2010). The knowledge of factors that may affect prenatal gonad development can allow management that improves the physiological and reproductive profile of an animal.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about spermatogenesis and testicular physiology is fundamental to understanding the factors that interfere with sperm production and the identification of potential causes of infertility and subfertility in males (REYNOLDS; CATON, 2012). Sertoli cells produced during the fetal stage determine the quantity of germ cells evolved in spermatogenesis and are echoed in the sperm production volume during the adult life of an animal (SHARPE et al, 2003).…”
Section: Introductionmentioning
confidence: 99%